The Influence of Motivation, Religiosity and Work Environment on The Productivity of SME Actors In Islamic Economics Review - Wahyuni Khalida; Nurbaiti; Silalahi , Purnama Ramadani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to determine the influence of motivation, religiosity, and work environment on the productivity of micro, small, and medium enterprises (MSMEs) in Gayo Lues Regency from the perspective of Islamic Economics. The research method used was quantitative research, utilizing primary data collected through questionnaire distribution to respondents, and secondary data sourced from the Ministry of Cooperatives and SMEs and literature studies from relevant books and research journals. Data analysis employed validity test, reliability test, classical assumption test, and hypothesis testing. The findings indicate that motivation does not significantly influence the productivity of MSMEs in Gayo Lues Regency. However, religiosity and work environment significantly influence MSMEs' productivity in Gayo Lues Regency. Simultaneously, motivation, religiosity, and work environment jointly affect productivity.